A molecular scale analysis of TEMPO-oxidation of native cellulose molecules. Issue 12 (December 2020) - Asgarpour Khansary, Milad; Pouresmaeel-Selakjani, Peyman; Aroon, Mohammad Ali; Hallajisani, Ahmad; Cookman, Jennifer; Shirazian, Saeed
Abstract: The native cellulose, through TEMPO (2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical)-mediated oxidation, can be converted into individual fibers. It has been observed that oxidized fibers disperse completely and individually in water. It is believed that electrostatic repulsive forces might be responsible for such observations. In order to study the TEMPO-oxidation of cellulose molecules, we used Density Functional Theory (DFT) calculations and Flory-Huggins theory combined with molecular dynamics (MD). The surface electrostatic potential in native cellulose and TEMPO-oxidized cellulose were calculated using DFT calculations. We found that TEMPO-oxidized cellulose accommodates a threefold screw conformation where the negatively charged (–COO–) functional groups are pointed away from the surface in all spatial directions. This spatial orientation causes that TEMPO-oxidized cellulose molecules repulse each other due to strong negatively charged surface. At the same time, the spatial orientation increases the hydrophilicity in TEMPO-oxidized cellulose molecules. These observations explain the improved dispersion in water and separability of TEMPO-oxidized cellulose molecules. We obtained large and positive Flory–Huggins interaction parameters for TEMPO-oxidized cellulose molecules indicating their higher dispersion once in water. Abstract : Cellulose; TEMPO oxidation; Density functional theory; Molecular dynamics; Surface modification